A Conceptual Analysis of Effective Gig Works System for Sustainable Employment in Challenging Times - JAAFAR, SYUHAIDA BT MOHAMED@; MAT, NIK HAZIMAH BT NIK (The journal of contemporary issues in business and government, 2021)
World today is having a crisis on global health issue and business environment’s uncertainty that significantly affected people’s income and survival. Further, job losses and unemployment are among the problems that influence the ability of the community to fulfil their household needs and wants. One way to manage the crisis is by providing employment opportunities that offer a stable income for the household to meet their financial expenses from time to time. In Malaysia, the Bottom 40 (B40) community group is the most affected by the current economy situation. The higher cost of living and lower level wages rate also add to the struggle of the community to live their life and forced the people to find an alternative work to survive the increased financial expenses. Gig- economy is an emerging labour market where the employer engages with the independent employees for short term contracts or also known as a freelancer. This new employment trend offers potentials for job creations to solve unemployment issue in the community especially during the challenging times. The underlying assumptions of four established theories in human resources management field are used to guide the articulation of the proposed framework. A conceptual analysis for an effective gig works system towards sustainable income for the community is discussed based on the current situations and Malaysian contextual elements.